Topofilias e topofobias marinhas na ‘Odisseia’: os ‘nautai’ como homens da ‘métis’, os deuses e as técnicas náuticas no contexto de fundação das ‘apoikiai’ (séc. X-VII a. C.) - Soares, Martinho Guilherme Fonseca (2020)
This work discusses the representation elaborated by Homer and, by extension, by the men of that time, regarding the sea as a topophilia and topophobia place. The research is in charge of investigating the events which, narrated in the Odyssey, recover th